Bioelectric activity of the brain and the predictive importance of effects of neurobiofeedback course at athletes - Cherapkina, L. (Journal of Human Sport & Exercise, 2018)
Works of the last years show activity of scientists on introduction of neurofeedback training in process of athletes training. At the same time, authors emphasizethe need of further carrying out researches for this field of knowledge, first of all, caused by insufficiency of empirical data. The purpose of work was identification of athletes' brain features of bioelectric activity, and determination of the importance of neurofeedback effects in effectiveness forecasting of their competitive activity. With 101 athletes the neurofeedback course directed to increase in power of EEG in the alpha range by means of a hardware and software system of "BOSLAB-ALFA" was conducted. Prior to a training and after its termination by means of the 19-channel electroencephalograph "Neuron Range 3" "background" EEG registered. After a neurofeedback course the effectiveness of competitive activity at each athlete which was considered as successful was estimated if exceeded the result received at the same rank previous competitions. The statistical analysis of the obtained data was carried out by means of software packages of "StatPack" and "SPSS 13". Results of the conducted research have allowed to distinguish the peculiar "the athlete's encephalographic portrait" which is characterized by more expressed activity in a theta - and delta ranges, the insufficient relative power of brain bioelectric activity in the alpha range. And also toestablish the informative indicators of post-training changes of EEG determining distinctions by success of competitive activity with an accuracy of recognition of 100%.